2022
DOI: 10.1038/s41420-022-00849-1
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 overexpression aggravates LPS-induced cellular inflammation in mouse intestinal epithelial cells and DSS-induced IBD in mice

Abstract: The inflammatory bowel diseases (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), are chronic inflammatory disorders of the intestine. Dysregulated cytokine secretion and signal transduction mechanisms via intestinal epithelial cells are involved in IBD pathogenesis, in which the transcription factor NF-κB plays a critical role. In this study, METTL3, which plays a key role in inflammation regulation, has been recognized significantly up-regulated in IBD samples, DSS-induced IBD mice, and LPS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…METTL3, a well‐known m 6 A modification writer, is a necessary catalytic subunit modulating m 6 A modification 47 . METTL3 was upregulated in CD colon tissues compared to NC tissues, consistent with Yang et al 48 . The close m 6 A modification and inflammation connection have attracted much attention.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…METTL3, a well‐known m 6 A modification writer, is a necessary catalytic subunit modulating m 6 A modification 47 . METTL3 was upregulated in CD colon tissues compared to NC tissues, consistent with Yang et al 48 . The close m 6 A modification and inflammation connection have attracted much attention.…”
Section: Resultssupporting
confidence: 76%
“…46 METTL3, a wellknown m 6 A modification writer, is a necessary catalytic subunit modulating m 6 A modification. 47 METTL3 was upregulated in CD colon tissues compared to NC tissues, consistent with Yang et al 48 The close m 6 A modification and inflammation connection have attracted much attention. A previous study in human dental pulp cells has shown that METTL3 can suppress the inflammatory response caused by LPS by modulating the alternate splicing of MyD88.…”
Section: In Vitro Function Of Circprkar1bsupporting
confidence: 83%
“…41 Mounting evidence has demonstrated the beneficial effects of RELA (p65) on the intestinal epithelial cell survival, inflammation resolution, and intestinal barrier maintenance in UC. [42][43][44] In this study, we identified that the artificial upregulation of RELA, both in the 3% DSS-induced mice and LPS-induced NCM-460 cells, significantly blocked the alleviating roles of Nexrutine from all aspects.…”
Section: Discussionmentioning
confidence: 70%
“…LPS has also been reported to be associated with UC. [ 31 ] LPS upregulated ST6GAL1 gene expression. An increase in pro‐inflammatory cytokines and a decrease in anti‐inflammatory cytokines often lead to UC.…”
Section: Discussionmentioning
confidence: 99%